2001
DOI: 10.1104/pp.010550
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis pxa1 Mutant Is Defective in an ATP-Binding Cassette Transporter-Like Protein Required for Peroxisomal Fatty Acid β-Oxidation

Abstract: Peroxisomes are important organelles in plant metabolism, containing all the enzymes required for fatty acid ␤-oxidation. More than 20 proteins are required for peroxisomal biogenesis and maintenance. The Arabidopsis pxa1 mutant, originally isolated because it is resistant to the auxin indole-3-butyric acid (IBA), developmentally arrests when germinated without supplemental sucrose, suggesting defects in fatty acid ␤-oxidation. Because IBA is converted to the more abundant auxin, indole-3-acetic acid (IAA), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
275
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(288 citation statements)
references
References 69 publications
9
275
0
4
Order By: Relevance
“…35 In A. thaliana, 3 independent experimental approaches have identified the same peroxisomal transporter, named CTS /PXA1/PED3, as responsible for the translocation of at least part of the fatty acids for b-oxidation. 31,38,39 It has been suggested that CTS /PXA1/PED3 might not be the only transporter for b-oxidation substrates into the peroxisome 34 and a LTP may be reasonable implicated in this process. A mayor concern to consider this hypothesis is the subcellular location of LTP3.…”
Section: Resultsmentioning
confidence: 99%
“…35 In A. thaliana, 3 independent experimental approaches have identified the same peroxisomal transporter, named CTS /PXA1/PED3, as responsible for the translocation of at least part of the fatty acids for b-oxidation. 31,38,39 It has been suggested that CTS /PXA1/PED3 might not be the only transporter for b-oxidation substrates into the peroxisome 34 and a LTP may be reasonable implicated in this process. A mayor concern to consider this hypothesis is the subcellular location of LTP3.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid metabolism in Arabidopsis roots and stems has received rather less attention than in leaves (LiBeisson et al, 2013). Our analysis of the pxa1 mutant, which is severely deficient in fatty acid b-oxidation (Zolman et al, 2001), showed that it also accumulates TAG in its roots. This suggests that b-oxidation does make a detectable contribution to the bulk turnover of fatty acid from membrane lipids in this tissue under normal growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…PXA1 is a peroxisomal ATPbinding cassette transporter that is required for fatty acid import for b-oxidation (Zolman et al, 2001), and CGI58 is an enzyme that has been reported to have lipase, phospholipase, and lysophosphatidic acid acyltransferase activities (Ghosh et al, 2009). Analysis of TAG content in pxa1-1 and cgi58-1 roots showed that both accumulated TAG, but not as much as sdp1-5 (Fig.…”
Section: Tag Accumulation In Sdp1 Roots Is Greater Than In Several Otmentioning
confidence: 99%
See 1 more Smart Citation
“…Indole-3-butyric acid (IBA), one of several auxin precursors in plants (for review, see Korasick et al, 2013), is converted in peroxisomes to the active auxin indole-3-acetic acid (IAA; Zolman et al, 2000;Strader et al, 2010;reviewed in Strader and Bartel, 2011). IBA-derived auxin is important during seedling development, when it influences lateral rooting (Zolman et al, 2001;De Rybel et al, 2012), cotyledon and root hair expansion, and apical hook formation (Strader and Bartel, 2009;Strader et al, 2010.…”
Section: B-oxidation: Not Just For Fatty Acidsmentioning
confidence: 99%